Legal Protection of Copyright Based on Law Number 28 of 2014 Concerning Copyright - Maria Tambunan; Bernat Panjaitan; Nimrot Siahaan (International Journal Labs, 2023)
One of the issues that arise in this free trade era is in the field of intellectual property rights. Intellectual property rights are becoming an issue in the context of today's international trade. This research aims to protect the law of copyright and know and analyze the juridical consequences of moral rights and economic rights from the act of transferring copyright. This research belongs to the normative type of research. So it can be known that in Law Number 28 of 2014 concerning Copyright, criminal and civil sanctions have been stipulated for everyone who commits copyright infringement, then the juridical consequence of moral rights and economic rights from the act of copyright transfer is that moral rights remain with the creator even though there has been a transfer of copyright in any form. Legal protection for copyright holders through licenses can lead to multiple interpretations in their application.